The Influence of Information on the Profit Response Coefficient in Indonesian Stock Exchange Companies - Saprudin Saprudin; Azaluddin Azaluddin (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This research aims to determine whether total compensation and wages significantly influence the benefit reaction coefficient of mining organizations listed on the Indonesia Stock Exchange for the 2020-2022 period. The method used is the multiple linear regression analysis method, but before entering this method, testing will first be carried out using descriptive analysis and classical assumption tests. This research was carried out by taking data on the Indonesian Stock Exchange, namely the official website of the Indonesian Stock Exchange. The research results show that the two independent variables, namely net profit and loss and operating profit and loss, do not have a significant influence on the profit response coefficient. Net profit and loss for mining companies listed on the Indonesian stock exchange has a significant value of 0.32, which means it is below 0.05. Meanwhile, the variable lab loss from operations has a significant value of 0.729, which means it is above the value of 0.05. The author suggests that future researchers can use a longer observation period and add other variables that influence the earnings response coefficient and investors should pay attention to significant financial variables that influence the earnings response coefficient.